Rational design of allosteric inhibitors targeting C797S mutant EGFR in NSCLC: an integrative in silico and in-vitro study - Jian Wang; Feiyang Yuan; Mahadevi Kendre; Zhijin He; Shaowei Dong; Abhinandan Patil; Kausing Padvi (Frontiers in Oncology)
BackgroundThe emergence of the C797S mutation in the epidermal growth factor receptor (EGFR) significantly limits the efficacy of covalent inhibitors in treating non-small cell lung cancer (NSCLC). This study aimed to design and evaluate novel allosteric inhibitors targeting the C797S mutant EGFR using advanced in silico methodologies.MethodsUtilizing scaffold hopping techniques, a library of compounds was generated based on the known allosteric inhibitor EAI045. Virtual screening identified 44 top-scoring compounds with strong binding affinities for the C797S mutant EGFR. Molecular docking studies evaluated binding interactions, while the MM-GBSA method assessed binding free energies. Additionally, pharmacokinetic properties were analysed using Lipinski’s rule of five, and the most promising compound, MK1, underwent molecular dynamics simulations followed by in-vitro assessmentResultsA total of 12 heterocyclic scaffolds were derived from EAI045, and 44 top-scoring compounds were identified through virtual screening and MM-GBSA analysis. MK1 demonstrated the highest docking score and a ΔG_bind of -29.36 kcal/mol, with strong interactions involving residues such as LYS728 and MET793. MD simulations over 100 ns confirmed the stability of the MK1-EGFR complex, with RMSD values stabilizing post-50 ns and RMSF values consistently below 3 Å. In-vitro assays validated MK1’s potent anticancer activity, showing significant cytotoxicity against C797S mutant cell lines, with IC50 values lower than the standard comparator. Additional pharmacokinetic profiling indicated MK1 adhered to Lipinski’s Rule of Five with no violations, highlighting its drug-like properties.ConclusionThe findings highlight MK1 as a promising candidate for the treatment of NSCLC harbouring the C797S mutation, providing valuable insights for future drug design and development strategies targeting mutant EGFR.